Combating land degradation for sustainable smallholder agriculture and food sovereignty in Ghana’s Volta Region - Armstrong Francis Tumawu; George Yao Kafu; Anthony Kangah; Mary Magdalene M. Tumawu (Frontiers in Sustainable Food Systems)
The severe and accelerating loss of land quality and productivity is widely acknowledged at all geographic scales, from the global scale down to the local level, across the world. Global food yield has decreased by 13% as a result of the 40% moderate degradation and 9% severe degradation of agricultural land. This study examines the dynamics of land degradation and its impacts on smallholder agriculture and food sovereignty in Ghana’s Volta Region, focusing on the Ho Municipality. Employing a mixed-methods approach, the research combines remote sensing analysis, quantitative surveys of 200 smallholder farmers, and qualitative interviews with experts and farmers. Findings reveal a concerning trend of increasing land degradation, with areas experiencing degradation rising from 2% in 2013 to 5% in 2023. The study demonstrates significant impacts on crop yields and farm income, with 87% of surveyed farmers reporting negative effects on their crop production due to land degradation. Smallholder farmers have adopted various coping strategies, with compost application (62.5%) and chemical fertilizer use (60%) being the most prevalent practices. The research highlights a discrepancy between scientific measurements and farmers’ perceptions of land degradation, emphasizing the importance of integrating local knowledge with technical assessments. The study contributes to the existing literature by providing a detailed, localized analysis of land degradation dynamics and their implications for smallholder agriculture and food sovereignty in the region. It offers valuable insights for policymakers and practitioners, underscoring the urgent need for targeted interventions to address land degradation while supporting sustainable agriculture and food security in Ghana and similar contexts.